SOUND ASSIMILATION IN AMANATUN DIALECT OF UAB METO - Wulandari, Heidi (International Journal of Humanity Studies (IJHS), 2019)
This study was conducted to identify and describe the kinds of assimilation in Amanatun Dialect of Uab Meto. Descriptive qualitative was used in conducting the study. The data were collected from Uab Meto native speaker’s speech transcription and analyzed using category identification and integration. The result of this study indicates that there are ten kinds of assimilation in Amanatun dialect of Uab Meto which are grouped into five classifiers. They are phonological assimilation and morphophonemic assimilation which are grouped into assimilation based on form; regressive assimilation and progressive assimilation which are grouped into assimilation based on direction, contact assimilation and distance assimilation which are grouped into assimilation based on distance, assimilation in word and assimilation at word boundary which are grouped into assimilation based on position, consonant assimilation and vowel-consonant assimilation which are grouped into assimilation based on inventory of sound.DOI: 10.24071/ijhs.2019.030104